ЗНИЖЕННЯ НЕРІВНОМІРНОСТІ НАГРІВАННЯ ТОРЦЕВОГО ПАКЕТА ОСЕРДЯ СТАТОРА ПОТУЖНОГО ТУРБОГЕНЕРАТОРА - Кенсицький, О.Г.; Хвалін, Д.І.; Сорокіна, Н.Л. (Інститут електродинаміки Національної академії наук України, 2018)
The mathematical model of heat-exchange processes in the end laminating stator core sheets of high-power turbo-generator is developed. The heating of the teeth in the interfacial area and outside the area is analyzed. The ways to reduce the tangential non-uniformity and levels of heating of the stator core teeth are proposed. The directed redistribution of cooling hydrogen stream along with increased transverse thermal conductivity gives a possibility to decrease the total heating of the end stator core sheets by 15 %. References 7, figures 6, tables 2.